Compound Dihuang Granule Inhibits Nigrostriatal Pathway Apoptosis in Parkinson’s Disease by Suppressing the JNK/AP-1 Pathway - Wang, Li; Yang, Yu-fang; Chen, Long; He, Zhu-qing; Bi, Dian-yong; Zhang, Lei; Xu, Yan-wu; He, Jian-cheng (Frontiers in Pharmacology, 2021)
Compound Dihuang Granule (CDG) is widely used in traditional Chinese medicine (TCM) for the treatment of Parkinson’s disease (PD) and has been definitively shown to alleviate PD symptoms. However, the molecular basis of its action is unclear. To explore the molecular mechanism of CDG against PD, we used TCM network pharmacology methods to predict its molecular targets and signaling pathways, followed by experimental validation. Protein-protein interaction (PPI) analysis identified 150 intersections between CDG and PD-related genes, comprised of 23 proteins including CASP3 (caspase-3), MAPK8 (JNK), FOS (c-Fos), and JUN (c-Jun). KEGG and GO analyses uncovered apoptotic regulation and MAPK signaling pathways as significantly enriched. Because c-Jun and c-Fos are subunits of AP-1, an important downstream effector of JNK, we investigated if the JNK/AP-1 pathway influences apoptosis of CDG via the nigrostriatal pathways in rats with PD. Molecular docking analysis found that the top three bioactive compounds exhibiting highest betweenness following online database and LC-MS analysis had high affinities for JNK. Experimental validation analysis showed that CDG decreased the number of rotating laps and suppressed the levels of phosphorylated c-Jun, c-Fos, JNK, as well as the number of TUNEL positive cells and the cleaved caspase-3 level in the nigrostriatal pathway. Additionally, CDG treatment elevated the number of TH neurons, TH expression, and Bcl-2/Bax protein ratio in a 6-OHDA induced PD in rat. Similar results were obtained using SP600125, a specific JNK inhibitor. In conclusion, CDG suppresses apoptosis via the nigrostriatal signaling pathway and relieves PD symptoms by suppressing JNK/AP-1 signaling.